Design and Application of a Test Rig for Stationary Component Performance Measurement of Centrifugal Compressors - K. Zhao; Y. Liu; Y. Zhang; X. Liu; H. Shi (Journal of Applied Fluid Mechanics)
Experimental testing is an important method for studying centrifugal compressors. However, test rigs with rotating impellers are costly in terms of construction and operating expenses. To address this issue, this study introduces a stationary component performance test rig for centrifugal compressors using an existing wind tunnel. The rig comprises a blower to supply compressed air, a wind tunnel, and a test section of stationary centrifugal compressor model stage. Specially designed stationary guide vanes substitute the impeller to simulate the impeller outlet flow field. Flow field parameters are measured at the inlet and outlet of each model-scale stationary component using a five-hole probe. Measured results can be used to evaluate the performance of each stationary component. Comparison between measured data and CFD results reveals that the measurement results are in good agreement with CFD results. This validates the reliability of the built test rig and measurement. Afterwards an improved diffuser and return channel of the same centrifugal compressor model stage is tested. The experimental results show a 4% reduction in total pressure loss coefficient and a 1% increase in static pressure recovery coefficient compared to the original structure. These results align with the findings obtained on a rotating test rig, indicating the feasibility of the proposed stationary component aerodynamic performance test rig.